Delivering the GOODs’: an empirical evaluation of the efficacy of supply chain sustainability initiatives of Grameenphone Limited - Ava, Tasneem Omar (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.